Evaluating presence in cultural heritage projects - Champion, Erik; Pujol, L. (Taylor Francis, 2012)
This paper surveys current notions of social and cultural presence as they may help the evaluation of cultural heritage projects. We argue that cultural heritage requires specialized evaluation, as key issues both connect and separate the aims of presence researchers and cultural heritage experts. To support this argument, three case studies of virtual heritage evaluations are summarized, and recommendations made as to how experimental design and evaluation may be improved for future projects.